Changes to bacterial communities and soil metabolites in an apple orchard as a legacy effect of different intercropping plants and soil management practices - Li, Xiaolong; Chu, Yannan; Jia, Yonghua; Yue, Haiying; Han, Zhenhai; Wang, Yi (Frontiers in Microbiology, 2022)
Intercropping is an important soil management practice for increasing orchard productivity and land-use efficiency because it has beneficial effects on soil microbial communities and soil properties. However, there is relatively little available information regarding the effects of different crops/grasses on soil microbial communities and soil metabolic products in apple orchards in arid and semi-arid regions. In this study, we first used third-generation PacBio SMRT long-read sequencing technology to evaluate the microbial communities of apple, intercropping plants, and sandy waste soil. Our results revealed that the microbial communities and soil metabolic properties differed significantly between apple and the sandy waste soil as well as the intercropping plants. Intercropping could significantly enrich diverse microbial species, as well as the microbial nitrogen and microbial carbon of soil Moreover, intercropping with licorice showed better effects in recruiting beneficial microbes compared to grass and pepper. Compared with grass and pepper, licorice significantly enriched species belonging to some well-known taxa with beneficial effects, including Bacillus, Ensifer, Paenibacillus, Rhizobium, and Sphingomonas. Thus, intercropping with licorice may improve apple tree growth and disease resistance. Furthermore, Bradyrhizobium and Rubrobacter were included among the keystone taxa of apple, whereas Bacillus, Chitinophaga, Stenotrophobacter, Rubrobacter, and Luteimonas were the keystone taxa of the intercropping plants. The results of our study suggest that intercropping with licorice is a viable option for increasing apple orchard productivity.